THE IMPACT OF MARINE TOURISM : A QUALITATIVE STUDY ON THE PERSPECTIVE OF THE LOCAL COMMUNITY IN LOVINA BALI - Luh Yusni Wiarti (Centre For Tourism Planning and Development, 2017)
Lovina is one of tourist destination situated on the northern part of Bali Island. It lies in the maritime area as Bali Golden Triangle Coral Reef line and belong to the central zone of water conservation area in Buleleng Regency, Bali. The aim of this paper is to explore the impact of marine tourism development for the community in Lovina area specifically in the aspect of social and culture with qualitative approach analysis through the local's perception. The survey was participated by 100 samples purposively assigned from local people who lived in Lovina. The result shows that the development of marine tourism in Lovina gives some positive impacts to the community in socio-cultural condition. Marine tourism development and activities do not deliver any harmful changes to the condition of building in Lovina area. It increases the enthusiasm of the community to perform religious activities of Hindu. In addition, the stress level and the crime figures are also very low. Various efforts are supposed to do in order to develop marine tourism activities in the region as well as minimizing the negative impact : 1) Improving the accessibilities by creating comfortable roads and parking lots as well as the addition of the trash bins which can helped by local government, 2) Educate the local community about The Concept of Sapta Pesona to improve their services to tourists and also educate them on the impact of marine tourism activities, thus they would be able to handle them, 3) Enhance the cooperation with stakeholders to market and promote Lovina.